Monopolar Diathermy Tonsillectomy Versus Dissection Method Tonsillectomy (KYAMC Journal, 2019)
Background: Tonsillectomy is one of the most common surgical procedures performed worldwide by otorhinolaryngologists for different indications. Tonsillectomy is often performed as day-case surgery, which increases the demands of a satisfactory postoperative pain control and a low risk of early postoperative bleeding.Objective: The aim of the study was to compare the Monopolar diathermy and Dissection methods of tonsillectomy and evaluate their advantages and disadvantages during surgery, convalescence.Materials and Methods: Two hundred children were recruited for this study during the period of five years from January, 2014 to December, 2018 at Otolaryngology department of Khwaja Yunus Ali Medical College and Hospital (KYAMCH). Subjects between the age of 5 and 25 years listed for tonsillectomy were included. Subjects were recommended not to have aspirin within the 2 weeks before surgery.Results: The mean duration of operation was found 10.6±0.4 minutes in group A and 17.0±0.7 minutes in group B. The difference was statistically significant (p